Differentiation of Dental Pulp Stem Cells into Neuron-Like Cells in Serum-Free Medium - Shahrul Hisham Zainal Ariffin; Shabnam Kermani; Intan Zarina Zainol Abidin; Rohaya Megat Abdul Wahab; Zulham Yamamoto; Sahidan Senafi; Zaidah Zainal Ariffin; Mohamad Abdul Razak (Hindawi Limited, 2013)
Dental pulp tissue contains dental pulp stem cells (DPSCs). Dental pulp cells (also known as dental pulp-derived mesenchymal stem cells) are capable of differentiating into multilineage cells including neuron-like cells. The aim of this study was to examine the capability of DPSCs to differentiate into neuron-like cells without using any reagents or growth factors. DPSCs were isolated from teeth extracted from 6- to 8-week-old mice and maintained in complete medium. The cells from the fourth passage were induced to differentiate by culturing in medium without serum or growth factors. RT-PCR molecular analysis showed characteristics of Cd146+, Cd166+, and Cd31− in DPSCs, indicating that these cells are mesenchymal stem cells rather than hematopoietic stem cells. After 5 days of neuronal differentiation, the cells showed neuron-like morphological changes and expressed MAP2 protein. The activation of Nestin was observed at low level prior to differentiation and increased after 5 days of culture in differentiation medium, whereas Tub3 was activated only after 5 days of neuronal differentiation. The proliferation of the differentiated cells decreased in comparison to that of the control cells. Dental pulp stem cells are induced to differentiate into neuron-like cells when cultured in serum- and growth factor-free medium.